2020
DOI: 10.3390/antiox9060537
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Status of the Cutaneous Endogenous and Exogenous Antioxidative System of Smokers and the Short-Term Effect of Defined Smoking Thereon

Abstract: The daily consumption of tobacco products leads to a boost in free radical production in tissues, promoting the risk for malignancies, metabolic alterations and chronic-inflammatory diseases. This study aimed to broaden the knowledge of the status of the antioxidative (AO) system in the skin, compared to the blood, of healthy appearing smokers. Both, the basic status compared to non-smokers and the short-term impact of controlled cigarette consumption in smokers were analyzed. Our study showed that the basic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
2
4
0
Order By: Relevance
“…Using non-invasive RRS and diffuse reflectance spectroscopy it was shown in human skin in vivo that the consumption of high doses of alcohol [ 186 ], excessive physical activity [ 187 ], domestic and work stress [ 52 , 188 , 189 ], and other stress factors [ 189 , 190 ] result in a reduction of the carotenoid concentration in the human SC, which depends on the initial concentration of the carotenoids’ and stressor’s intensity. It has been noticed that the concentration of carotenoids in the SC of smokers is significantly lower than in non-smokers ( p < 0.001) [ 135 , 191 , 192 ], which is in agreement with the literature data [ 50 , 193 , 194 ]. The concentration of carotenoids in the SC of women is significantly higher than in men ( p < 0.05) [ 192 ].…”
Section: Factors Resulting In the Reduction Of Carotenoids In The Scsupporting
confidence: 90%
See 1 more Smart Citation
“…Using non-invasive RRS and diffuse reflectance spectroscopy it was shown in human skin in vivo that the consumption of high doses of alcohol [ 186 ], excessive physical activity [ 187 ], domestic and work stress [ 52 , 188 , 189 ], and other stress factors [ 189 , 190 ] result in a reduction of the carotenoid concentration in the human SC, which depends on the initial concentration of the carotenoids’ and stressor’s intensity. It has been noticed that the concentration of carotenoids in the SC of smokers is significantly lower than in non-smokers ( p < 0.001) [ 135 , 191 , 192 ], which is in agreement with the literature data [ 50 , 193 , 194 ]. The concentration of carotenoids in the SC of women is significantly higher than in men ( p < 0.05) [ 192 ].…”
Section: Factors Resulting In the Reduction Of Carotenoids In The Scsupporting
confidence: 90%
“…However, recent investigations have shown that smokers may have a lower carotenoid concentration but higher k values in the SC. This was explained by the substantial increase of glutathione concentration in the upper SC of smokers compared to non-smokers and primarily the interaction of the skin probe TEMPO with the endogenous antioxidants [ 135 ]. Thus, in smokers, the skin probe TEMPO was reduced primarily by glutathione, resulting in a higher k value.…”
Section: Carotenoids Are Marker Substances Of the Antioxidant Status ...mentioning
confidence: 99%
“…Increased blood GSH levels have been shown in heavy smokers (>20 cigarettes a day). On the other hand, in people who smoked less than 20 cigarettes a day, the concentrations of glutathione were similar to those observed in the group of non-smokers [29,31,34].…”
Section: Discussionsupporting
confidence: 78%
“…The skin represents a reservoir for endogenous antioxidants as well as antioxidants obtained from dietary intake. [36]. Prior studies showed that a healthy nutrition rich in fruits and vegetables was associated with an enhanced cutaneous carotenoid content [37, 38] which corresponds to other literature that showed that carotenoids are suited biomarkers for fruit and vegetable intake [21].…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, the negative effect of smoking on the cutaneous carotenoid concentration was shown by a study of Meinke et al [35]. This effect was later more detailed on a biochemical level studied by Lohan et al and a promoted stress‐level by tobacco consumption was assumed, which consumed antioxidants from the bloodstream [36]. The reduced antioxidant levels in the skin of smokers versus non‐somkers are assumed as a result of a higher radical load by smoking which leads to a higher initial consumption of the antioxidants from the bloodstream.…”
Section: Discussionmentioning
confidence: 99%